EKSPERIMEN PEMBENTUKAN KERAK GIPSUM PADA PIPA BERALIRAN LAMINIR DENGAN PARAMETER LAJU ALIR DAN ADITIF ION CU2+ : KAJIAN KINETIS - Mangestiyono, Wiji; Bayuseno, A.P.; Muryanto, Stefanus (Gema Teknologi, 2011)
Wiji Mangestiyono, , A.P. Bayuseno, Stefanus Muryanto, in this paper explain that the problem of gypsum scaling becomes a trouble for some industry in which use some water for its system. Some disadvanteges come up because of : the time of industrial process will be more longer and production cost increase necesery.To prevent the growth of scale, the experiment must be done. Researcher try to answer this problem so an experimental about kinetic study of gypsum scaling established. Flowrate would be a parameter with assume that it has effect on reaction flow. The result of Â this experiment are : reaction rate increase when flow rate increase; adition some aditives becomes reaction rate decrease. Keywords : crystal, flow rate, reactio rate, gipsum